A Deep Learning Model For Dimension Reduction And Multi-Class Classification Of Gene Expression Data - Seal, Dibyendu Bikash; Mukherjee, Aradhita (International Journal of Computer Sciences and Engineering, 2025)
Gene expression analysis has been vital in cancer detection across the world. Genes regulating cell growth in cancer, suffer altered expressions. This leads to various phenotypic traits. Gene expression profiling has been extensively used by researchers to accurately identify tumours and has thus enabled better understanding of tumour biology. However, feature extraction and classification of gene expression datasets is challenging due to the high dimension of gene expression datasets and the non-linear relationships among the data. In this article, we have developed a deep learning-based dimension reduction and multi-class classification model using deep auto-encoder and multi-layer perceptron (MLP). We have trained the autoencoder to extract meaningful features from the RNA-Seq data. These features are then used for supervised classification of tumour samples using a multilayer perceptron. Our (deepAE-MLP) model showed better feature extraction and disease classification capabilities when compared to benchmark methods